The Effect of Leadership, Motivation, and Discipline On Employee Performance in The Banglen Layer Farming Industry in The Province in Yogyakarta - Vica Saputro; Tina Melinda (Universitas Ciputra Surabaya, 2021)
This research is done to find out the effect of leadership, motivation and discipline on employees’ performance in Banglen layer chicken farm in Yogyakarta province. The research method uses quantitative method in which data is obtained by distributing to all of Banglen Farming Chicken employees in Yogyakarta province offline questionnaires. The sample in this research uses saturation method, so this research uses 52 of all Banglen Farming employees as the respondents. The benchmark that is used to evaluate this research on questionnaire uses Likert scale. The test that is used in this research data analysis uses SPSS (Statistical Product and Service Solution) software. Based on the result of data analysis in this research, shows that leadership variable (X1) has significant value as 0.007 and T calculation of 2.826 on employees’ performance variable (Y), so be stated affects significant. Motivation variable (X2) has significant value of 0.008 and t calculation of 2.766 on the employees’ performance variable (Y) so be stated affects significant. Discipline variable (X3) has significant value as 0.068 and t calculation of 1.865 on the employees’ performance variable (Y).